Pre-dilapidation survey for infrastructure (road) at Bandar Sultan Suleiman, 42000, Port Klang, Selangor Darul Ehsan / Anis Sahira Baharuddin - Baharuddin, Anis Sahira (Universiti Teknologi MARA UiTM,Perak, 2021)
Jasa Sendi (M) Sdn Bhd was founded and established in 24th of May 1993 by Prof. Sr. Dr. Ahmad bin Ramly . He was a senior managerial and technical officer in Kuala Lumpur City Hall before serving as a professor of the Faculty of Built Environment, University of Malaya before establishing the company.Jasa Sendi (M) Sdn Bhd is a Chartered Building Surveying Consultancy firm that offers building consultancy and inspection services related to the fields of Building Dilapidation Survey, Asset Management, and Building Audit. The services provided are including building inspection, condition monitoring, performance assessment, maintenance, defects rectification, conservation, life cycle costing, reports for claims in consumer’s Tribunal, and also project management.